Public Spaces, Private Gardens : A History of Designed Landscapes in New Orleans - Douglas, Lake, 1949- (Book collections on Project MUSE., 2011)
Landscape architect Lake Douglas employs written accounts, archival data, historic photographs, lithographs, maps, and city planning documentsùmany of which have never been published until nowùto explore public and private outdoor spaces in New Orleans and those who shaped them. The result, Public Spaces, Private Gardens: A History of Designed Landscapes in New Orleans, is the first in-depth examination of the cityAEs landscape history. Douglas presents this ôbeautiful and imposingö city as a work of art crafted by numerous influences. A survey from the colonial period to the twentieth century.